Modelling primary proteolysis in cheddar cheese in commercial cool stores : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Bioprocess Engineering at Massey University - Edmonds, Richard (Massey University, 2000)
One issue identified as a possible problem during the manufacture of cheddar cheese is the possibility of producing a non-uniform product. It was proposed that a pallet of cheese experiencing different time-temperature histories, depending on the position within the pallet, could cause the heterogeneity. This work involved the investigation of that issue. The level of primary proteolysis observed in cheese was measured over time in cheeses of different compositions, stored at different temperatures. The remaining intact αₛ₁casein was measured using reverse phase high performance liquid chromatography. Several trends were observed during maturation. High temperatures caused a faster rate of disappearance of αₛ₁casein. The temperature relationship followed Arrhenius law. High moisture content caused a faster rate of the disappearance of αₛ₁casein. The level of rennet added to the milk during production had a directly proportional effect on the rate of the disappearance of αₛ₁casein. Salt had no observable effect in the range investigated here. From the data a kinetic model was developed that described the rate of disappearance of αₛ₁casein in terms of the temperature, the moisture content, and the level of rennet in the cheese. The heat transfer occurring in the commercial pallet of cheese was mathematically modelled and solved numerically. The heat transfer model was then applied to produce data describing the time-temperature profile throughout a pallet of cheese for a variety of possible industrial storage conditions. The kinetic model developed was then used to predict the extent of proteolysis in each case. It was found that there would be significantly different levels of proteolysis within a pallet of cheese that had undergone chilling. A 10% difference in the level of proteolysis between the surface and the centre was observed after chilling for 40 days. During freezing the difference in the level of proteolysis after freezing was complete ranged from 10-25%. It was found that the heterogeneity was reduced during the thawing process and that the greatest reduction in non-uniformity was observed when thawed at lower temperatures.
Keywords: Cheese; Cheddar cheese